The Current Link Between Management Behavior and Ethical Philosophy - Premeaux, Shane R. (Journal of business ethics, 2004)
The current linkages between ethical theory and management behavior are investigated. The vignettes used in this investigation represent ethical dilemmas in the areas of coercion and control, conflict of interest, physical environment, and personal integrity. Overall, even with heightened ethical awareness the link between ethical philosophy and management behavior remains similar to that of the early 1990s. Generally, practitioners still rely heavily on the utilitarian ethical philosophy when making business decisions. However, more managers are now likely to select ethically appropriate actions either because it is ethical to do so, or because the consequences or risk of not doing so are too great. This shift could positively impact the ethical climate of business decision-making.